TRAVELOGUE OF HADJI MUIN "MEMORY OF KATTAKURGON" (Scientific journal of the Fergana State University, 2023)
The article discusses the features of the guidebook of Hadji Muin, who fought for the development of the nation, called "Memories of Kattakurgan", information that attracts the reader's attention, in particular, the realities that Hadji Muin saw and witnessed during his trip to Kattakurgan, including the state of the empty reading room in Kattakurgan, holding back the progress of the nation, the situations and opinions on the author's subjective assessment of each of them are analyzed. It is also believed that the ideas of enlightenment in modern travelogues are built in a comparative method, and that the author used the theme of travel as an artistic device according to his creative concept in modern travelogues.